Tourist shoppers’ satisfaction with regional shopping mall experiences - LeHew, Melody L. A.; Wesley, Scarlett C. (My University, 2008)
This article assesses whether tourist shopper segments are an attractive market for shopping centers. The purpose of this research is to explore whether or not tourist shoppers are more satisfied than resident shoppers with their shopping experience and do tourist shoppers have the intention to spend more than their resident shopper counterparts. Data for this report come from personal face-to-face mall intercepts of shoppers (n = 578) in two new generation malls (West Edmonton Mall and Mall of America in Bloomington) and two heritage-destination (Pier 39 in San Francisco and Forum Shops in Las Vegas) centers. Analysis concludes that although the shopping center and retail industry place increasing emphasis on leisure shopping and tourism, the results of this study suggest that the tourist shopper market may not be the most valuable customer group. Resident shoppers of tourist-focused shopping centers are more satisfied than tourist shoppers of those centers. These findings should encourage shopping center managers to use caution when modifying strategies to meet the needs of the tourist segment, as well as to not forget the importance of resident shoppers to their profitability.
Keywords: Tourism; Shopping; Shopping centers; Customer satisfaction